2021
DOI: 10.1369/00221554211035192
|View full text |Cite
|
Sign up to set email alerts
|

Proteases Regulate Cancer Stem Cell Properties and Remodel Their Microenvironment

Abstract: Proteolytic activity is perturbed in tumors and their microenvironment, and proteases also affect cancer stem cells (CSCs). CSCs are the therapy-resistant subpopulation of cancer cells with tumor-initiating capacity that reside in specialized tumor microenvironment niches. In this review, we briefly summarize the significance of proteases in regulating CSC activities with a focus on brain tumor glioblastoma. A plethora of proteases and their inhibitors participate in CSC invasiveness and affect intercellular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 218 publications
(236 reference statements)
0
5
0
Order By: Relevance
“…As discussed in this Review, the inhibitors developed so far effectively inhibit the activity and/or function of ectoproteases originating from mature tumour cells, endothelial cells, as well as CAFs and immune cells. Recent studies have indicated that CSCs express DPP4, APN, ADAM17, and MMP2/9 [12,73,[234][235][236][237][238][239][240].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
“…As discussed in this Review, the inhibitors developed so far effectively inhibit the activity and/or function of ectoproteases originating from mature tumour cells, endothelial cells, as well as CAFs and immune cells. Recent studies have indicated that CSCs express DPP4, APN, ADAM17, and MMP2/9 [12,73,[234][235][236][237][238][239][240].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
“…Cathepsins have been shown to be strong predictive biomarkers for GBM patient survival [27,28,33]. In this study, high levels of cathepsin X do not correlate with survival of GBM patients, although we showed by its selective inhibition that cathepsin X promotes viability of GBM cells and GBM-associated macrophages and microglia as well as proliferation and invasion of GBM cells.…”
Section: Discussionmentioning
confidence: 54%
“…In tumors, the expression of lysosomal cysteine cathepsins is often elevated and is generally associated with poor patient prognosis [26]. Cathepsins have been shown to exert tumor-promoting functions [27], such as promoting tumor growth, invasion [28], and resistance to therapy [26,29], although some of them also contribute to tumor suppression [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…183 Recently, involvement of cell types and proteins in CSCs and in particular in GSCs has been reviewed, such as a novel cell type, the telocyte, 184 scaffold proteins, 185,186 the renin-angiotensin system, 187 and specific proteases and their endogenous inhibitors. 188 MSCs are another cell type that infiltrates glioblastoma tumors and are present in GSC niches, as they are in HSC niches in bone marrow (Fig. 5).…”
Section: Energy Metabolism Of Gscsmentioning
confidence: 99%